Pengaruh perbedaan komposisi bahan terhadap kualitas tekstur mi konjak - Ferdy Pratama; Bunga Raya Ketaren; Norzaleha Binti Kasim; Maisarah Binti Shamsulkamal (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Konjac noodles are functional foods characterized by low calorie content, high soluble fiber, and gluten-free properties. The textural quality of konjac noodles is highly dependent on differences in ingredient composition, particularly the interaction between konjac glucomannan (KGM), calcium hydroxide (Ca(OH)₂) as a cross-linking agent, and additional hydrocolloids or starch. This study aimed to examine the effect of variations in the composition of these ingredients on the textural quality of konjac noodles, as represented by tensile strength and elasticity. A factorial experimental design was applied using the same types of ingredients with varying proportions, and texture analysis was conducted using a texture analyzer. The results showed significant differences in textural properties among formulations. Batch F3 exhibited the highest tensile strength (24.08 g) and elasticity (−36.08 mm), indicating the formation of a strong and flexible gel structure with relatively low variability. Conversely, Batches F2 and F14 produced weak and unstable gel structures, while Batch F4 resulted in a rigid gel with limited elasticity. These findings indicate that the textural quality of konjac noodles is influenced by differences in ingredient composition, where an appropriate balance between tensile strength and elasticity is essential to obtain a stable and desirable texture.